Penguatan Identitas Nasional melalui Pemberdayaan Pemuda dalam Program Civic Action - Gaite, Titus (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2023)
Strengthening national identity among the younger generation is one of the key challenges in the era of globalization, particularly in regions with high socio-cultural diversity such as Ambon. This community service-based research aimed to empower students of SMA Negeri 3 Ambon through a civic action program as an applicative and participatory approach to civic education. The methods included training on national values, designing and implementing social projects within the school and surrounding community, as well as evaluations through pre-tests, post-tests, and interviews. The results showed increased understanding of national values, active student participation in social actions, and a transformation in attitudes, including a stronger sense of pride and responsibility as citizens. The program also successfully fostered tolerance and social solidarity amid Ambon’s diversity. In conclusion, civic action is an effective method for strengthening national identity and can be replicated in other schools with similar contexts to help preserve national unity and cohesion.